Безпека на автотранспорті: проблеми та перспективи - Степанов, О. В.; Наглюк, І. С. (НТУ "ХПІ", 2015)
У статті розглядаються особливості поняття безпеки на автомобильному транспорті та поняття транспортної безпеки. Наведені проблеми та перспективи безпеки на автотранспорті. Висвітлено широкий діапазон внутрішніх і зовнішніх загроз, що послаблюють транспортну безпеку країни. На ряду з поняттям загрози транспортної безпеки наведено класифікацію загроз транспортної безпеки. Зроблено висновок, що подальший розвиток транспортної системи та забезпечення її стабільного функціонування в умовах безпеки транспорту є стратегічним завданням держави.

The article discusses the features of the concept of safety in road transport and transport security concepts. The author tells about the problems and prospects of security on a vehicle. A wide range of internal and external threats that weaken the transport security of the country is examined in the article. Along with the concept of transport security threat one can find the classification of transport security threats. The author comes to the conclusion that further development of the transport system ensuring its stable operation in safety of transport is a strategic object of the country. Urgent problem of road safety. In road transport, due to the large number and mobility of vehicles, traffic safety problems are most acute. There is a tendency to a rapid deterioration of the situation that requires urgent response. In this connection, the security on the different types of vehicles is currently one of the priority requirements for transport systems.
Security by car: problems and prospects
Keywords: транспортна безпека; загрози; ДТП; GPS-трекінг; road transport; road transport safety; transport safety